The Effect of Using Digital-Based Comic Learning Media on Reading Literacy for Grade 4 Elementary School Students: Pengaruh Pemanfaatan Media Pembelajaran Komik Berbasis Digital Terhadap Literasi Membaca Siswa Kelas 4 Sekolah Dasar - Maghfiroh, Asyharina; Wachidah, Kemil (Indonesian Journal of Innovation Studies, 2023)
In this study, it aims to determine the influence of the use of digital-based comic learning media on the reading literacy of grade IV students of SD Negeri Damarsi. This research uses experimental research methods which are part of quantitative approach research is usually used to find the influence of a treatment on a subject or object. Experimental research with a quantitative approach in this study was used to determine the influence of the use of digital-based comic learning media on the reading literacy of grade IV students of SDN Damarsi. Learning media in experimental classes and reading text learning media in control classes. Both classes are assumed to be homogeneous in terms of equal learning ability and differ in terms of the treatment given. This research uses experimental research with a Quasi Experimental Research design. Data collection in this study used tests in the form of pre-test and post-test. And from the results of this study showed that there was a positive and significant influence after learning for 4 times and with the pre-test & post test activities, it was concluded that class IV A during the pre-test produced an average score of 72.27. For the results of the pre-test class IV B, the average score is 69.51. Then the two classes held a post test. Class IV A average resulting score was 88.53. For class IV B the average resulting score is 73.60.